2009
DOI: 10.2460/ajvr.70.4.547
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of glomerular filtration rate in dogs by plasma clearance of gadolinium diethylenetriamine pentaacetic acid as measured by use of an ELISA

Abstract: OBJECTIVE-To evaluate use of gadolinium diethylenetriamine pentaacetic acid (Gd-DTPA) to estimate glomerular filtration rate (GFR) by plasma clearance and use of an ELISA as the method of Gd-DTPA quantification. ANIMALS-16 dogs of various sexes and breeds (12 dogs were clinically normal, and 4 dogs were polyuric and polydipsic with no other clinical or biochemical abnormalities). PROCEDURES-GFR was estimated by measuring the plasma clearance of Gd-DTPA and iohexol by use of an ELISA and high-performance liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…GFR was evaluated using the FIT‐GFR Inulin Kit and a one‐compartment plasma clearance method (BioPhysics Assay Laboratory; BioPAL, Worcester, MA, USA) according to the manufacturer's instructions and as previously described . Briefly, mice were injected with GFR‐grade inulin (5 mg/kg; IP).…”
Section: Methodsmentioning
confidence: 99%
“…GFR was evaluated using the FIT‐GFR Inulin Kit and a one‐compartment plasma clearance method (BioPhysics Assay Laboratory; BioPAL, Worcester, MA, USA) according to the manufacturer's instructions and as previously described . Briefly, mice were injected with GFR‐grade inulin (5 mg/kg; IP).…”
Section: Methodsmentioning
confidence: 99%
“…In cats, two-and four-sample plasma clearance of iohexol has also provided accurate results when compared with plasma clearance of exogenous creatinine (Heiene et al, 2009). Finally, gadolinium, a contrast agent used for magnetic resonance imaging contrast studies, may be useful as an alternative marker to iohexol either via direct measurement of plasma clearance or when bound to a radionuclide, but studies are limited at this time (Magnotti et al, 2009; Nolan et al, 2009). …”
Section: Markers and Techniques For Gfr Determinationmentioning
confidence: 99%
“…We applied magnetic resonance imaging (MRI) to further estimate the integrity of the glomerular filtration barrier in Atgl(À/À) mice. Gadopentetic acid (GdDTPA) is excreted by glomerular filtration, and it has been reported that the plasma clearance of GdDTPA is an effective method to estimate glomerular filtration rate (GFR) [17]. Figure 3A,B shows inversion-recovery T1 maps in which T1 relaxation time was inversely proportional to the content of GdDTPA retained in the kidney tissue.…”
Section: Atgl Deficiency Destroys the Integrity Of The Glomerular Filmentioning
confidence: 99%